2001
DOI: 10.1377/hlthaff.20.5.252
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes About Genetic Testing For Alzheimer’s Disease

Abstract: In a general population survey (N = 314), 79 percent of respondents stated that they would take a hypothetical genetic test to predict whether they will eventually develop Alzheimer's disease. The proportion fell to 45 percent for a "partially predictive" test (which had a one in ten chance of being incorrect). Inclination to obtain testing was similar across age groups. Respondents were willing to pay $324 for the completely predictive test. Respondents stated that if they tested positive, they would sign adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 19 publications
4
96
0
6
Order By: Relevance
“…The desire for certainty is also reflected in the studies that measured interest in genetic testing or willingness to take a genetic test for AD. Studies found that the majority of participants would have testing if it was 100% accurate or fully predictive, while only a small number of participants would be interested in testing that was only partially accurate or predictive (Neumann et al, 2001;Hipps et al, 2003).…”
Section: Apoe Susceptibility Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The desire for certainty is also reflected in the studies that measured interest in genetic testing or willingness to take a genetic test for AD. Studies found that the majority of participants would have testing if it was 100% accurate or fully predictive, while only a small number of participants would be interested in testing that was only partially accurate or predictive (Neumann et al, 2001;Hipps et al, 2003).…”
Section: Apoe Susceptibility Testingmentioning
confidence: 99%
“…Three articles examined the attitudes of the general population to susceptibility testing fcir AD (Frost et al, 2001;Neumann et al, 2001;Hipps et al, 2003), and five studies assessed attitudes in individuals with a family history of AD (Cutler and Hodgson, 2003;Roberts et al, 2003;Bassett et al, 2004;Moscarillo et al, 2007;Christensen et al, 2011). Generally these attitudinal studies show high levels of interest in hypothetical testing for APOE; for example, Bassett et al (2004) found that 72% of individuals with a family history of AD would choose to have a genetic test if 1t was offered to them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of Alzheimer's disease (AD), survey respondents have reported willingness to pay on average between $120 and $500 for predictive AD testing, depending upon the accuracy and prior risk conditions of hypothetical scenarios (Neumann et al, 2001(Neumann et al, , 2010. However, no studies have asked individuals about WTP for susceptibility genetic testing after they have demonstrated their interest and had an opportunity to value the experience by actually undergoing such testing.…”
mentioning
confidence: 99%
“…In a recent general population survey, more than two-thirds of respondents stated that they would purchase long-term care insurance were they to learn from a completely predictive genetics test that they would contract Alzheimer's disease. 5 With regard to confidentiality, Congress adopted a provision, as part of the Health Insurance Portability and Accountability Act (HIPAA) of 1996, prohibiting health insurers from using genetic information in making eligibility determinations. 6 However, to date the US Department of Health and Human Services' efforts to implement the HIPAA medical privacy and confidentiality provisions are confused and contentious.…”
Section: Controls On Access To Informationmentioning
confidence: 99%